Expanding the scope of shared decision-making in vascular access planning for hemodialysis: a case for interprofessional collaboration - Andrea Yu-Ling Liu; Mary Hammes; Peter Angelos; Neil Kondamuri; Lauren Harriett; Ashley Suah; Ted Albert Skolarus (BMC Nephrology)
Abstract Vascular access planning guidelines have shifted from a fistula-centered to a patient-centered approach. We advocate for expansion of the shared decision-making dyad between the nephrology team and patient to include other vascular access planning stakeholders. We propose earlier and consistent interprofessional collaboration facilitates more constructive discussions that could improve outcomes.